Detection and prevalence of parasites in creole cattle from a rural area in an Andean district of Peru. - Rojas-Moncada, J. (2025)
Animals raised in rural areas often lack sufficient healthcare and nutrition due to limited access to professional services or state programs. This situation is worsened by extensive grazing practices, which expose cattle to parasites. This study aimed to identify helminths and coccidia by examining fecal eggs and oocysts in creole cattle from small-scale producers raised under grazing conditions at altitudes above 3,000 m in the rural area of Chota district, Cajamarca, Peru. Fecal samples from 385 cattle were analyzed, with 357 (92.73 ± 2.59%) testing positive for parasite eggs and oocysts. At the farm level, all (37/37) were infected with parasites. Natural sedimentation identified eggs of Fasciola hepatica (19.48 ± 3.96%). Flotation concentration using a saturated sugar solution revealed eggs of strongylid-like nematodes (SLN) (81.56 ± 3.87%), Capillaria spp (1.82 ± 1.33%), Trichuris spp (2.86 ± 1.66%), Toxocara vitulorum (2.08 ± 1.42%), Moniezia spp (8.05 ± 2.72%), and oocysts of Eimeria spp (55.58 ± 4.96%). The parasitic load of SLN and Eimeria spp was associated with sex and showed a moderate negative correlation with age (p < 0.05). Females exhibited an odds ratio (OR) of 0.393 [95%CI 0.187 - 0.825] for SLN infection, OR = 0.298 [95%CI 0.177 - 0.503] for Eimeria spp, and OR = 2.206 95%CI 1.111 - 4.382] for F. hepatica compared to males (p < 0.05). Younger cattle had a higher probability of infection with SLN, Moniezia spp, and Eimeria spp while showing a lower likelihood of F. hepatica infection than those older than four years (p < 0.05). The initial study conducted in the rural area of the Chota district revealed a high frequency of infections by various internal parasites in creole cattle, but with low parasite loads. These findings suggest further research on whether parasite loads impact animal health or production.